Perlakuan Akuntansi Akad Musyarakah Mutanaqisah (Studi Kasus : KPR iB Pada Bank Muamalat Cabang Darmo Surabaya) - Aishanafi Khadifya Sarwedhie; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Islamic bank is one of the services industry who offer products according to Shariah requirements. To meet the challenges and muamalah phenomena that exist in current business. Regulators, academics, practitioners, and Sharia Board are required to innovate the products that will be offered to customers. One such innovation is the emergence of hybrid contracts (multi-contract), where in the contract occurred several contract transacted. Application of the hybrid contract with the Bank Muamalah Indonesia is that using the KPR iB financing musharaka mutanaqisah contract (MMQ).Of these phenomena, this research intend to see out of the side of accounting applied in transactions using MMQ contract. This study aims to determine the accounting treatment on Musharaka mutanaqisah contract by Bank Muamalat Indonesia on KPR iB products and verify compliance whether the accounting treatment in accordance with PSAK No. 106 and DSN No. 73.The results of this research make findings that the accounting treatment was carried out by BMI for start-up capital is recognized as a capital MMQ cash. This is because the factors of positive law in force in Indonesia that have an impact on the next accounting treatment, installments process and when the end of the contract. In addition, the realization of the contract is not in harmony with the accounting treatment, so the accounting treatment can not describe what is going on in the contract because it can be obstruction by the positive law applicable. But overall accounting treatment has been carried out by BMI in accordance with PSAK No. 106 and DSN No. 73 on the MMQ installments process and when the contract expires. REFERENCESAgustianto. September 2011. Hybrid Contract dalam Keuangan dan Perbankan Syariah Kontemporer. Sharing, hlm. 14-19.Agustianto. Hybrid pada Pembiayaan Properti (MMQ). Makalah disajikan dalam Pelatihan Akad Hybrid Contract pada Produk Keuangan Syariah. Hotel Mercure. Surabaya. Desember 2011.Antonio, Muhammad Syafi’i. Banks Syariah Wacana Utama dan Cendikiawan. 1999. Jakarta: Tazkia Institute.Aris, Nooraslinda Abdul, Rohana Othman, Rafidah Mohd Azli, Roshayani Arshad, Mardiyyah Sahri2 and Abdul Razak Yaakub. 2011. Islamic house financing: Comparison between Bai’ Bithamin Ajil (BBA) and Musharakah Mutanaqisah (MM). African Journal of Business Management. VI (9): 266- 273.Aryani, Ayu Layla. 2011. Perlakuan Akuntansi Terhadap Pembiayaan dengan Prinsip Mudharabah dan Musyarakah pada Bank Syariah (Studi Kasus pada PT Bank Muamalat Indonesia Cabang Syariah). Skripsi tidak diterbitkan. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Basri, Ikhwan Abidin. Syirkah/ Musyarakah, (http://www.tazkia.co.id, diakses 2 Maret 2011).Ghazaly, Abdul Rahman, dkk. Fiqh Muamalat. 2008. Jakarta: Kencana Prenada Media Group.Ghuddah, ‘Abd al-Sattar Abu. 2005. Musharakah Mutanaqishah and Its Shari’ah Parameters. Makalah disampaikan dalam Fifteenth Session of the International Islamic Fiqh Academy of the OIC. Musqat, Oman.Hassan, A. Bulughul Maraam. 2001. Bangil: Pustaka Tamaam.Hosen, M Nadratuzzaman Hosen. 10 September 2013. www.ekonomisyariah.org.Kuncoro, Mudrajad. 2003. Metode Riset untuk Bisnis dan Ekonomi. Jakarta: Erlangga.Mas’adi, Ghufron. Fiqh Muamalah Kontekstual. 2002. Jakarta: Rajawali Pers.Moleong, Lexy J. 2000. Metode Penelitian Kualitatif. Bandung: PT. Remaja Rosdakarya.Pradipta, Raissa Almira. 2011. Tinjauan Terhadap Pengalihan Porsi Kepemilikan dan Hak Sewa dari Nasabah kepada Pihak Ketiga Dalam Perjanjian Pembiayaan Pemilikan Rumah (PPR iB) yang Menggunakan Akad Musyarakah Mutanaqisah (Studi Kasus Bank Muamalat Indonesia). Disertasi tidak diterbitkan. Depok Fakultas Hukum Universitas Indonesia.Saeed, Abdullah. Tanpa Tahun. Menyoal Bank Syariah Kritik Atas Interpretasi Bunga Bank Kaum Neo-Revivalis. Terjemahan oleh Arif Maftuhin. 2004. Jakarta: Paramadina.Saipudin, Afif. 2009. Perlakuan Akuntansi Terhadap Pembiayaan dan Pendanaan dengan Prinsip Mudharabah pada Bank Syariah (Studi Kasus pada Bank Syariah Mandiri Jakarta). Disertasi tidak diterbitkan. Surabaya Fakultas Ekonomi dan Bisnis Universitas Airlangga.Shihab, M. Quraish. 2009. Tafsir Al-Mishbah. Volume 3. Ciputat: Lentera Hati.Smolo, Edib & M. Kabir Hassan. 2011. The Potentials of Musharakah Mutanaqisah for Islamic Housing Finance. Emerald, 4(3): (237-258).Sugiyono. 2005. Memahami Penelitian Kualitatif. Bandung Alfabeta.Suhendi, Hendi. Fiqh Muamalah. 2010. Jakarta: Rajawali Pers.Yin, Robert K. 2002. Studi Kasus : Desain dan Metode, Terjemahan. Jakarta: PT Grafindo Persada.